1993
DOI: 10.1111/j.1749-6632.1993.tb22936.x
|View full text |Cite
|
Sign up to set email alerts
|

Seronegative Myasthenia Gravis: Evidence for Plasma Factor(s) Interfering with Acetylcholine Receptor Functiona

Abstract: CLINICAL OBSERVATIONSSNMG must first be distinguished from congenital myasthenic syndromes. The latter usually present at birth or within the first two years, do not respond to a J. Burges and R. Barrett-Jolley were supported by Action Research for the Crippled

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 14 publications
2
26
1
Order By: Relevance
“…Three pieces of evidence demonstrate that seronegative MG patients probably have antibodies that bind to another distinct muscle membrane target, closely associated with the AChRs at the neuromuscular junction. First, their sera inhibit AChR function in an acute, but transient, manner [52] and this inhibition is very similar to that found with addition of calcitonin gene related peptide and adrenergic agonists that act through G protein-coupled receptors [52,53] and lead to AChR desensitization [54]. This indicates that the antibodies can activate second messengers leading to AChR phosphorylation; phosphorylation of AChRs has been demonstrated in preliminary studies (P. Plested, T. Tang & A. Vincent, unpublished results).…”
Section: Seronegative Mgsupporting
confidence: 57%
“…Three pieces of evidence demonstrate that seronegative MG patients probably have antibodies that bind to another distinct muscle membrane target, closely associated with the AChRs at the neuromuscular junction. First, their sera inhibit AChR function in an acute, but transient, manner [52] and this inhibition is very similar to that found with addition of calcitonin gene related peptide and adrenergic agonists that act through G protein-coupled receptors [52,53] and lead to AChR desensitization [54]. This indicates that the antibodies can activate second messengers leading to AChR phosphorylation; phosphorylation of AChRs has been demonstrated in preliminary studies (P. Plested, T. Tang & A. Vincent, unpublished results).…”
Section: Seronegative Mgsupporting
confidence: 57%
“…Hence, although the well-known defect in neuromuscular transmission is the main cause of weakness and enhanced fatigue of muscles in MG patients, defects in E-C coupling and contractility may also play an important part in enhancing the fatigue. Furthermore, our studies indicate that such extrajunctional defects may play a significant role in the weakness and enhanced fatigue in patients with seronegative MG. 39,52 …”
Section: Dlscusslonmentioning
confidence: 98%
“…However, these patients, too, respond to plasma exchange and immunosuppressive therapy,2g and diaphragm muscles from mice injected with Ig from SMG patients show increased sensitivity of neuromuscular transmission to ~-t u b o c u r a r i n e .~~ Drachman and coworkers found that there was some reduction in muscle AChRs in SMG muscle, 8 as we have also found in several cases. 36 Drachman et al also showed that both mepp amplitudes and Seronegative Myasthenia Gravis "'I-cL-BuTx were reduced in mice injected with Ig from 3 SMG patients. * In contrast, diaphragm muscles from mice injected with Ig from 10 SMG patients showed increased sensitivity of neuromuscular transmission to D-tubocurarine without any substantial change in '251-a-BuTx binding.,' Collectively, these findings point to an autoantibodymediated disorder of neuromuscular transmission in SMG patients, but do not clearly indicate the site of action.…”
mentioning
confidence: 97%